Towards renewable energy through justifications: How the aim of advancing the transition to renewable energy sources has been used to justify measures hindering renewable energy trade in the European Union. - Frimodig, Alex (My University, 2025)
This bachelor’s thesis examines the relationship between the aim of advancing the transition to renewable energy and restrictions on renewable energy trade. Often national schemes or mechanisms create barriers to trade, which are forbidden by article 34 of the Treaty on the Functioning of the European Union. However, the Court of Justice of the European Union has often justified these barriers on the grounds of overriding requirements in the public interest relating to the protection of the environment, even if the measures were distinctly applicable. In this paper I argue that due to the aims of recent legislation and the entire EU, these justification for restrictions on renewable energy trade are compatible with the internal market. This construction is based on doctrinal research of relevant legislation, case-law, the opinions of Advocate Generals and literature. The insufficient expression of the exception to the general rule governing justifying measures having equivalent effect to quantitative restrictions by recourse to overriding requirements in the public interest is discussed in this thesis.

Tämä notaarityö tarkastelee uusiutuvaan energiaan siirtymisen tavoittelun ja uusiutuvan energian kaupan rajoitusten välistä suhdetta Euroopan unionin oikeuden näkökulmasta. Usein kansalliset järjestelmät ja mekanismit voivat luoda Euroopan unionin toiminnasta tehdyn sopimuksen 34. artiklassa kiellettyjä esteitä kaupalle. Euroopan unionin tuomioistuin on kuitenkin usein oikeuttanut näitä esteitä ympäristönsuojeluun liittyvillä yleisen edun mukaisilla pakottavilla vaatimuksilla esteiden avoimesti syrjivästä luonteesta huolimatta. Väitän viimeaikaisen lainsäädännön ja koko Euroopan unionin tavoitteiden perusteella, että uusiutuvan energian kauppaa rajoittavien toimenpiteiden oikeutukset ovat yhteensopivia sisämarkkinan kanssa. Tulkinta perustuu oikeusdogmaattiseen lainsäädännön, asiaankuuluvan oikeuskäytännön, julkisasiamiesten lausuntojen ja kirjallisuuden tutkimukseen. Työssä otetaan myös kantaa ympäristönsuojelun yhteydessä esiintyvän määrällisiä rajoituksia vaikutukseltaan vastaavien toimenpiteiden oikeuttamista koskevan yleisen säännön poikkeuksen riittämättömään ilmaisuun.
Keywords: Energy, Renewable energy, Sustainability, European Union, Internal market, Justifications, Free movement of goods